SOLUSI POLINOMIAL TAYLOR DARI PERSAMAAN INTEGRAL VOLTERRA - Nasution, Lisa Anna; Deswita, Leli; Lily, Endang (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
We discuss a polynomial solution of linear and nonlinear Volterra integral equations by stating their solutions in the form of a Taylor series. Furthermore, the coefficients of the Taylor series are determined by solving a system of linear equation. Then by inserting these coefficients into the Taylor series, we obtained a polynomial solution of linear and nonlinear Volterra integral equations in a simple form.